The concave versus convex approach for minimally invasive lateral lumbar interbody fusion for thoracolumbar degenerative scoliosis. Issue 10 (October 2015) - Scheer, Justin K.; Khanna, Ryan; Lopez, Alejandro J.; Fessler, Richard G.; Koski, Tyler R.; Smith, Zachary A.; Dahdaleh, Nader S.
Abstract We retrospectively reviewed patient charts to compare the approach-related (convex versus concave) neurological complications and magnitude of correction in patients undergoing lateral lumbar interbody fusion (LLIF). It is yet to be quantitatively determined if correction of adult degenerative scoliosis from either side of the curve apex using a LLIF results in a reduction in complications and/or improved corrective ability. The inclusion criteria for this study were patients who underwent a LLIF for adult degenerative thoracolumbar scoliosis and had the LLIF prior to any other supplemental procedures. Patients were grouped based on the approach toward the curve apex concavity (CAVE) or the convexity (VEX). Standard coronal and sagittal radiographic measurements were made. Neurological complications and reoperation indications were also recorded. We included 32 patients for review (CAVE: 17; VEX: 15) with a mean age of 65.5 years ± a standard deviation of 10.2, and mean follow-up of 17.0 months ± 15.7. There were eight postoperative neurological complications in eight patients (25.0%), and seven reoperations for six patients (18.8%; CAVE: 4/17 [23.5%]; VEX: 2/15 [13.3%]). The CAVE group had 6/17 neurological complications (35.3%; four ipsilateral and two contralateral to approach side) and VEX had 2/15 (13.3%; one ipsilateral and one bilateral to approach side; p > 0.05). All patients significantly improved in the mean regional and segmental Cobb angles (p < 0.05), except for T11–T12 (p > 0.05). There were no significant differences between the groups for any of the radiographic parameters measured (p > 0.05). Approaching the curve apex from either the concave or convex side resulted in significant improvements. The concave approach was associated with more postoperative neurological complications.